2005
DOI: 10.1111/j.1551-2916.2005.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies for Preparing NanoSized Silicon Nitride Ceramics

Abstract: We report the preparation of nanosized silicon nitride (Si3N4) ceramics via high‐energy mechanical milling and subsequent spark plasma sintering. A starting powder mixture consisting of ultrafine β‐Si3N4 and sintering additives of 5‐mol% Y2O3 and 2‐mol% Al2O3 was prepared by high‐energy mechanical milling. After milling, the powder mixture was mostly transformed into a non‐equilibrium amorphous phase containing a large quantity of well‐dispersed nanocrystalline β‐Si3N4 particles. This powder precursor was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 25 publications
3
60
0
Order By: Relevance
“…10 Recent reports have shown that mechanochemical activation can be applied to compounds such as sialons, in which mixtures of the component nitrides and hydroxides, when milled in a planetary mill at 400 rpm for 48 h and subsequently heated at 1600 • C form a variety of sialon products. 11 On the other hand, a mixture of halloysite and fine carbon powder after similar mechanochemical activation was exposed to carbothermal reduction, resulting in the formation of the expected sialon products in the temperature range 1200-1400 • C. 12 Milling at 475 rpm of a low z-value sialon precursor mixture 13 and of ␤-Si 3 N 4 with alumina and yttria sintering additives 14 resulted in a non-equilibrium amorphous phase containing many well-dispersed nanocrystalline ␤-Si 3 N 4 particles 14 which could be consolidated to a fully dense ceramic by spark plasma sintering at 1550-1600 • C for 5 min.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recent reports have shown that mechanochemical activation can be applied to compounds such as sialons, in which mixtures of the component nitrides and hydroxides, when milled in a planetary mill at 400 rpm for 48 h and subsequently heated at 1600 • C form a variety of sialon products. 11 On the other hand, a mixture of halloysite and fine carbon powder after similar mechanochemical activation was exposed to carbothermal reduction, resulting in the formation of the expected sialon products in the temperature range 1200-1400 • C. 12 Milling at 475 rpm of a low z-value sialon precursor mixture 13 and of ␤-Si 3 N 4 with alumina and yttria sintering additives 14 resulted in a non-equilibrium amorphous phase containing many well-dispersed nanocrystalline ␤-Si 3 N 4 particles 14 which could be consolidated to a fully dense ceramic by spark plasma sintering at 1550-1600 • C for 5 min.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al 17 Coe et al 32 found an inverse relationship between hardness and grain size in the case of hot pressed Si 3 N 4 . Xu et al 33 sintered nano-sized Si 3 N 4 using spark plasma sintering (SPS) at 1600 • C for 5 min at a heating rate of 300 • C/min and obtained elevated hardness and the authors correlated the high hardness value with fine grain structure (70 nm). The results of indentation fracture toughness measurements are presented in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…After the start of shrinkage, degree and rate in the shrinkage of milled powder became much higher than those of as-mixed powder. This difference in densification manner may be caused by the small grain size of Si 3 N 4 and the vitrification of Si 3 N 4 , Y 2 O 3 , and Al 2 O 3 [20].…”
Section: Article In Pressmentioning
confidence: 99%
“…The SPS technique was used in most of the studies performed after 2000 [18][19][20][21]23,[25][26][27][28]. This technique is similar to hot pressing; however, it is different from hot pressing in terms of the heating process.…”
Section: Densificationmentioning
confidence: 99%
See 1 more Smart Citation